The Developmental Phenotype of the Great Toe in Fibrodysplasia Ossificans Progressiva - Towler, O. Will; Kaplan, Frederick S.; Shore, Eileen M. (Frontiers in Cell and Developmental Biology, 2020)
Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disorder in which extensive heterotopic ossification (HO) begins to form during early childhood and progresses throughout life. Although HO does not occur during embryonic development, children who carry the ACVR1R206H mutation that causes most cases of FOP characteristically exhibit malformation of their great toes at birth, indicating that the mutation acts during embryonic development to alter skeletal formation. Despite the high prevalence of the great toe malformation in the FOP population, it has received relatively little attention due to its apparently clinically benign nature. In this study, we examined radiographs from a cohort of 41 FOP patients ranging from 2 months to 48 years of age to provide a detailed analysis of the developmental features, progression, and variability of the great toe malformation of FOP, which include absent skeletal structures, malformed epiphyses, ectopic ossification centers, malformed first metatarsals and phalangeal fusion.